PROMOTION OF THE REGION BY FOREIGN INVESTMENT - Acewicz, Mirosław (Ekonomia i Prawo. Economics and Law, 2013)
Globalization of the world usually starts with the economic, capital and production relations. Locating foreign investment in different regions starts their promotion. Self-promotion just by the sheer existence of something in a certain environment is implemented identity and image dimensions. Pomotion identity is the identity of the region in the context of changes of its economic and social potential, whereas an image is a visible sign of wealth and the success of the entire territory perceived as a chance for, and at the same time,the result of regional investments.